On the Asymptotic Formula of a Bessel’s Functions Product in Intermodulation Analysis - Xie Zhongjie (Tongxin xuebao)
A probability proof of an asymptotic formula of Bessel’s functions product is given. The asymptotic formula, while used for intermodulation analysis, would save a lot of computing time.